Distribution of the deaths from childhood and adolescent cancer across the regional health agencies from the Rio de Janeiro State, Brazil / Distribuição de óbitos de câncer infanto-juvenil nas regionais de saúde do Estado do Rio de Janeiro - Aline Cerqueira Santos Santana da Silva; Bianka Queiroz da Silva; Rayssa Goulart Valente; Virginia Maria de Azevedo Oliveira Knupp; Leila Leontina do Couto Bárcia; Isabel Cristina Ribeiro Regazzi (Universidade Federal do Estado do Rio de Janeiro, 2021)
Objective: The study's main purpose has been to analyze the spatial distribution of deaths from malignant neoplasms in patients aged up to 19 years old across the regional health agencies of Rio de Janeiro State. Methods: This ecological study analyzed the spatial distribution of deaths from January to December 2015 through data of the Sistema de Informações sobre Mortalidade (SIM) [Mortality Information System]. The data were tabulated in Tabnet and analyzed using the R statistical software. Results: Considering the 101 deaths observed, 24 (23.8%) were from central nervous system cancer. The Metropolitan I regional health agency had the highest death rates (63.3%), and Baixada Litorânea had the highest proportion of deaths from leukemia (27.9%). Conclusion: Identifying the most frequent deaths from malignant neoplasms makes it possible to formulate public policies aimed at prevention, diagnostics, and treatment consistent with the local reality.